2018
DOI: 10.1016/j.vaccine.2017.10.108
|View full text |Cite
|
Sign up to set email alerts
|

Innovative vaccine delivery strategies in response to a cholera outbreak in the challenging context of Lake Chilwa. A rapid qualitative assessment

Abstract: A reactive campaign using two doses of Shanchol Oral Cholera Vaccine (OCV) was implemented in 2016 in the Lake Chilwa Region (Malawi) targeting fish dependent communities. Three strategies for the second vaccine dose delivery (including delivery by a community leader and self-administration) were used to facilitate vaccine access.This assessment collected vaccine perceptions and opinions about the OCV campaign of 313 study participants, including: fishermen, fish traders, farmers, community leaders, and one he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…An anthropological survey carried out in parallel suggested that the innovative strategy was not well understood by some community leaders and, thus, communication with the community was poor. 12 …”
Section: Discussionmentioning
confidence: 99%
“…An anthropological survey carried out in parallel suggested that the innovative strategy was not well understood by some community leaders and, thus, communication with the community was poor. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The FGD guide included a set of predetermined questions covering topics on perception of cholera causation, vaccines, and OCV acceptability; practices to prevent and treat cholera; and logistical inputs on space and timeline of vaccine delivery. The FGD Guide was designed on the basis of qualitative assessments of OCV campaigns in Malawi and Mozambique conducted by two authors of this paper [28, 29]. One Research Assistant facilitated the FGD while another recorded and took notes.…”
Section: Methodsmentioning
confidence: 99%
“…However, a cholera outbreak that affected all regions of Malawi from October 2017 to March 2018 resulted in few or no cases in Nsanje, Chikwawa and the Lake Chilwa area, all which have had almost annual outbreaks with moderate-to-high incidence since 2001, but had been recently vaccinated ( Table 1 ). 6 , 7 …”
Section: Relevant Changesmentioning
confidence: 99%
“…4 In the light of increased global availability of the vaccine, in 2015 the global cholera vaccine stockpile 4 , 5 was extended for use in areas experiencing recurrent cholera outbreaks. Emergency vaccination campaigns, including campaigns in Malawi, 6 , 7 have largely been conducted with the support of nongovernmental organizations (NGOs), with little integration into local health systems. Vaccine use in areas with recurrent cholera transmission provides an opportunity for comprehensive cholera prevention integrated with government health and infrastructure programmes.…”
Section: Introductionmentioning
confidence: 99%